Contribuições da teoria pedagógica histórico-crítica para o ensino de literatura: uma leitura comparativa de pesquisas - Almeida, Sâmella Priscila Ferreira (2021)
This is a theoretical-bibliographical study, with a materialist-historical-dialectical approach, which aimed to understand the contributions of historical-critical pedagogical theory to the teaching of literature, based on an integrative bibliographical review. The papers analyzed were primarily from the Capes (Coordination for the Improvement of Higher Education Personnel) Catalogue of Theses and Dissertations, which directly related “Teaching Literature” and/or “Literary Reading” to “Historical-Critical Pedagogy”. We took the assumption of historical-critical pedagogy that the task of school education is to identify the most developed forms of objective knowledge produced historically, in order to convert them into school knowledge, transmissible and assimilable in the school environment, in order to allow the singular man the humanization that is generic to him. Based on this assumption, we developed the indices that guided the reading and analysis of the research found, namely: 1) How and why working with literature is important for human development; 2) How to identify and choose the content to be worked on in literature classes; 3) How to make this content transmissible and assimilable, adapting it to the material possibilities of the teacher's work. Based on these indicators, we have systematized contributions produced in the field of historical-critical pedagogy for the teaching of literature, carrying out a comparative and critical reading of what has been done so far and, where possible, pointing out the pressing tasks for the coming years.